Polymer Coatings of Cochlear Implant Electrode Surface – An Option for Improving Electrode-Nerve-Interface by Blocking Fibroblast Overgrowth - Hadler, C.; Aliuos, P.; Brandes, G.; Warnecke, A.; Bohlmann, J.; Dempwolf, W.; Menzel, H.; Lenarz, T.; Reuter, G.; Wissel, K. (PLOS ONE, 2016)
Overgrowth of connective tissue and scar formation induced by the electrode array insertion increase the impedance and, thus, diminish the interactions between neural probes as like cochlear implants (CI) and the target tissue. Therefore, it is of great clinical interest to modify the carrier material of the electrodes to improve the electrode nerve interface for selective cell adhesion. On one side connective tissue growth needs to be reduced to avoid electrode array encapsulation, on the other side the carrier material should not compromise the interaction with neuronal cells. The present in vitro-study qualitatively and quantitatively characterises the interaction of fibroblasts, glial cells and spiral ganglion neurons (SGN) with ultrathin poly(N,N-dimethylacrylamide) (PDMAA), poly(2-ethyloxazoline) (PEtOx) and poly([2-methacryloyloxy)ethyl]trimethylammoniumchlorid) (PMTA) films immobilised onto glass surfaces using a photoreactive anchor layer. The layer thickness and hydrophilicity of the polymer films were characterised by ellipsometric and water contact angle measurement. Moreover the topography of the surfaces was investigated using atomic force microscopy (AFM). The neuronal and non-neuronal cells were dissociated from spiral ganglions of postnatal rats and cultivated for 48 h on top of the polymer coatings. Immunocytochemical staining of neuronal and intermediary filaments revealed that glial cells predominantly attached on PMTA films, but not on PDMAA and PEtOx monolayers. Hereby, strong survival rates and neurite outgrowth were only found on PMTA, whereas PDMAA and PEtOx coatings significantly reduced the SG neuron survival and neuritogenesis. As also shown by scanning electron microscopy (SEM) SGN strongly survived and retained their differentiated phenotype only on PMTA. In conclusion, survival and neuritogenesis of SGN may be associated with the extent of the glial cell growth. Since PMTA was the only of the polar polymers used in this study bearing a cationic charge, it can be assumed that this charge favours adhesion of both glial cells and SG neurons glial cells and SGN.